Mathematical Apparatus for Error Probability Determination of Block Code Decoders - Maria Franekova (Communications - Scientific letters of the University of Zilina, 2001)
This paper deals with safety – related communication in closed transmission systems when block systematic (n, k) safety codes are used. The mathematical apparatus for calculation of probability of undetected sequence error is described for codes, with known and unknown weight structure. The numerical results are valid for a Symmetric Binary Channel when the occurrence of independent errors is assumed.